Association of Transfer RNA Fragments in White Blood Cells With Antibody Response to Bovine Leukemia Virus in Holstein Cattle - Taxis, Tasia M.; Kehrli, Marcus E.; D’Orey-Branco, Rui; Casas, Eduardo (Frontiers in Genetics, 2018)
Bovine leukemia virus (BLV) affects cattle health and productivity worldwide, causing abnormal immune function and immunosuppression. Transfer RNA fragments (tRFs) are known to be involved in inhibition of gene expression and have been associated with stress and immune response, tumor growth, and viral infection. The objective of this study was to identify tRFs associated with antibody response to BLV in Holstein cattle. Sera from 14 animals were collected to establish IgG reactivity to BLV by ELISA. Seven animals were seropositive (positive group) and 7 were seronegative (negative group) for BLV exposure. Leukocytes from each animal were collected and tRFs were extracted for sequencing. tRF5GlnCTG, tRF5GlnTTG, and tRF5HisGTG, were significantly different between seropositive and seronegative groups (P< 0.0067). In all cases the positive group had a lower number of normalized sequences for tRFs when compared to the negative group. Result suggests that tRF5s could potentially be used as biomarkers to establish exposure of cattle to BLV.